(untitled) (Research, Society and Development, 2020)
The objective of this literature review is to highlight the main aspects of the fish’s innate immune system, demonstrating the need for new alternatives for disease control, respecting the premise of sustainability, with the use of biologically active immunostimulants. In fish there is no presence of myeloid tissues or organs, the components of your immune system are classified only as lymphoids, and innate immunity is considered the organism’s first line of defense against the pathogen. Thus, the use of food additives and immunostimulants help to improve the natural immune system of these animals. They can be synthetic, chemical or biological substances that induce the activation or increase of components of the immune system, thus providing early defense against diseases, and can be used as preventive treatment. Vegetable compounds, essential oils and bioactive plant strata have great potential, as they have proven antimicrobial and antiparasitic functions. Among them, garlic is considered one of the most effective, as it acts as a growth promoter, appetite stimulator, antimicrobial, antioxidant and immune stimulant, it also helps with hematological parameters and increases the well-being of fish, as well as the ability to improve meat quality and extend shelf life.